Unwriting Food Labels: Discursive Challenges in the Regulation of Package Claims. (October 2014) - Jones, Rodney H.
This article examines the challenges resulting from the regulation of written discourse on food packages. It uses as a case study Hong Kong's strict new food-labeling law that requires distributers and retailers to remove certain nutritional claims from packages of imported food before they sell them. This practice of redacting unlawful text on packages requires that distributers and retailers engage in complex processes of discursive reasoning, and it sometimes results in packages that are difficult for customers to interpret. The case study highlights important issues in the regulation of commercial texts concerning collaboration, intertextuality, and the conflicts that can arise when the principals, authors, and animators of such texts have different agendas.